Effects of intra-egg injection of vitamin c on the eggshell mineral absorption, embryo mortality and hematological variables in chicks at hot incubation temperature - Sgavioli, Sarah [UNESP]; de Almeida, Vitor Rosa [UNESP]; Praes, Maria Fernanda F.M. [UNESP]; Iara Vicentini, Tamiris [UNESP]; Matos Junior, Joao Batista [UNESP]; Morita, Viviane de Souza [UNESP]; Malheiros, Euclides Braga [UNESP]; Boleli, Isabel Cristina [UNESP] (My University, 2013)
This study examined whether preincubation injection of vitamin C intra-eggs influences the eggshell mineral absorption, embryo mortality and hematological characteristics of chicks from eggs incubated at usual or hot temperatures. Five hundred fertile eggs from broiler breeder (Cobb®) were used in an experiment consisting of a 5 x 2 factorial arrangement (five treatments: no injection or injection of 0%, 4, or 6% vitamin C/100 pL water; two incubation temperatures: 37.5°C and 39.0°C). The percentages of vitamin C injected into the eggs did not influence the hematological characteristics of the chicks when compared to non-injected controls. However, chicks from eggs injected with 4% vitamin C had a higher total number of Red Blood Cells (RBCs) and levels of Hematocrit (HCT) and Hemoglobin (HGB) when incubation occurred at hot temperatures. The lowest percentage of Phosphorus (P) from the eggshells incubated at hot temperatures was observed with 2% vitamin C and the highest with 6% vitamin C. Embryo mortality was higher in eggs injected with 2 and 4% of vitamin C than in eggs not injected with vitamin C. The data indicate that intra-eggs injected vitamin C influences the phosphorus absorption from the shell and injection of 4% vitamin C improves potential gas transport in the blood of chicks from eggs incubated at hot temperatures but increases the embryo mortality. © Asian Network for Scientific Information, 2013.
Keywords: Ascorbic acid; Blood ph; Erythrogram; Heat stress